Foreign exchange operations and its contribution to the growth of Jamuna Bank Limited - Emon, Md. Rafsan Jany (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.